2017
DOI: 10.1097/md.0000000000008349
|View full text |Cite
|
Sign up to set email alerts
|

Decreased haptoglobin levels inversely correlated with pulmonary artery pressure in patients with pulmonary arterial hypertension

Abstract: We investigated the serum haptoglobin levels in patients with pulmonary arterial hypertension (PAH) based on the hypothesis that haptoglobin levels would reflect subclinical hemolysis due to microangiopathy in pulmonary arterioles.This cross-sectional study included 3 groups of patients attending Hokkaido University Hospital: PAH, chronic thromboembolic pulmonary hypertension (CTEPH), and connective tissue diseases (CTD) without PAH (CTD-non-PAH) group. Serum haptoglobin levels were measured by standardized tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Moreover, in another study, plasma free haemoglobin, was independently associated with increased risk for admission to hospital in PAH groups 28 . Furthermore, decreased levels of haptoglobin are seen in PAH phenotypes suggesting increased haemoglobin binding and removal in these patients 29 which is likely related to enhanced or on-going haemolysis. Studies presented herein suggest that free haemoglobin is also a pro-proliferative agent for hPASMCs and that the first description of the presence of CD163 on these cells suggests a means for cellular uptake of this iron containing protein complex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in another study, plasma free haemoglobin, was independently associated with increased risk for admission to hospital in PAH groups 28 . Furthermore, decreased levels of haptoglobin are seen in PAH phenotypes suggesting increased haemoglobin binding and removal in these patients 29 which is likely related to enhanced or on-going haemolysis. Studies presented herein suggest that free haemoglobin is also a pro-proliferative agent for hPASMCs and that the first description of the presence of CD163 on these cells suggests a means for cellular uptake of this iron containing protein complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that microvascular lesions cause diabetic ophthalmopathy and nephropathy and that DM-induced vascular injuries are a key factor in the development of microvascular lesions (8). Vascular endothelial cells serve important roles in maintaining the integrity of vascular structure and function (9,10). Patients with DM often exhibit damages to vascular endothelial cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Except for the functions mentioned above, HAP also inhibits prostaglandin synthesis, antioxidant activity, promoting immune function, and angiogenesis. [27][28][29] Atsumi et al 30 have reported that serum HAP levels decreased in PH patients and inversely correlated with pulmonary artery pressure in PH related to connective tissue diseases (CTD) patients, suggesting their potential as a surrogate marker for PH-CTD. Buehler et al 31 have found that chronic HAP infusion was a novel therapy for chronic hemolysis-associated PH by preventing Hb-mediated vascular remodeling associated with hypoxia.…”
Section: Discussionmentioning
confidence: 99%